The Influence of Price and Service Quality on Consumer Purchase Intention at Indomaret in Baubau City - Muhdir, Muhdir; Sanusi, Sanusi; Sarlin, Sarlin; Fatwa, Rahyu (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
This study aims to determine the impact of pricing and service quality on consumer purchase intentions at Indomaret in Baubau City. A quantitative research framework was used, with survey techniques as the primary method for obtaining data from research participants. Data were obtained by distributing questionnaires to 96 consumer respondents selected using random sampling. The collected data were then analyzed using multiple linear regression using SPSS version 26 software. The results indicate that both price and service quality influence consumers’ purchase intention at Indomaret in Baubau City. Price was found to be a more dominant factor affecting purchase intention than service quality. These findings suggest that consumers tend to consider price affordability and price suitability when determining their purchase intention, while service quality remains an important factor in creating a positive shopping experience. Overall, competitive pricing and high-quality service can enhance consumers’ purchase intention. Therefore, Indomaret should maintain an appropriate pricing strategy and continuously improve its service quality to encourage greater consumer purchase intention.